Exploring Global Trends of Research on Organizational Resilience and Sustainability: A Bibliometric Review - Abdullahi, Usman; Mohamed, Ahmad Martadha; Senasi, Vally (Universiti Utara Malaysia Press, 2023)
The current research presents a bibliometric review of publications on organizational resilience and sustainability publications using the Scopus database for the period 1998–2022 based on the corresponding keywords in the titles of the articles. In this study MS Excel was used for frequency analysis; Harzing’s Publish or Perish to analyze citations and their metrics, while VOSviewer and Bibliometric R-tool with Biblioshiny were employed for visualization and thematic analysis. According to the findings, research on organizational resilience and sustainability gained prominence in 1998 and has steadily increased since 2005. The United States of America recorded the most productive and highest contribution, followed by the United Kingdom. The Journal of Sustainability Switzerland has published the most papers, while the University of Canterbury, New Zealand, is the most productive institution. This research used the Scopus database. Other data sources may be accessed later, and searches may include summaries and keywords instead of document titles. To the best of the author’s knowledge, this is one of the first bibliometric review studies combining organizational resilience and sustainability research in the Scopus database.